PENGARUH KEPEMILIKAN KELUARGA TERHADAP PROFITABILITAS DENGAN FIRM SIZE, FIRM LEVERAGE DAN SALES GROWTH SEBAGAI VARIABEL KONTROL - Bryan Anderson Tombilayuk; Yulius Jogi Christiawan (Business Accounting Review, 2017)
The purpose of this research was to determine whether the ownership of the family affected profitability with firm size, leverage, and sales growth as control variables. This study was conducted on companies all sectors listed in BEI during 2012 to 2015 with the number of sample 357 or the number of observations of 1428 fiscal years. The analysis technique used was multiple linear regression with E-views software. The results found that family ownership had no affect on profitability. Menwhile, firm size, leverage, and sales growth were found to have affect on profitability.